1998
DOI: 10.1007/s002650050454
|View full text |Cite
|
Sign up to set email alerts
|

The roles of echolocation and olfaction in two Neotropical fruit-eating bats, Carollia perspicillata and C. castanea , feeding on Piper

Abstract: We studied the echolocation and foraging behavior of two Neotropical frugivorous leaf-nosed bats (Carollia perspicillata, C. castanea: Phyllostomidae) in ā ight cage. To test which cues Carollia uses to detect, identify, and localize ripe Piper fruit, their preferred natural food, we conducted experiments under seminatural conditions with ripe, unripe, and arti®cal fruits. We ®rst oered the bats ripe fruits and documented their foraging behavior using multi¯ash stereophotography combined with simultaneous soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
226
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(242 citation statements)
references
References 48 publications
10
226
1
5
Order By: Relevance
“…If the beginning of fruiting influences the start of breeding in C. perspicillata, one could suppose that plants might produce some substance, probably not nutritive, which could act as a stimulus for the beginning of estrus. It has already been reported that Carollia bats use volatile substances produced by Piper plants as a clue to find mature fruits (Thies et al, 1998;Mikich et al, 2003). Besides, Dechaud et al (1999) and Breinholt et al (2000) suggested that flavinoids might be strong stimulants for mammalian reproduction, because they contain estrogen-like substances.…”
Section: Discussionmentioning
confidence: 99%
“…If the beginning of fruiting influences the start of breeding in C. perspicillata, one could suppose that plants might produce some substance, probably not nutritive, which could act as a stimulus for the beginning of estrus. It has already been reported that Carollia bats use volatile substances produced by Piper plants as a clue to find mature fruits (Thies et al, 1998;Mikich et al, 2003). Besides, Dechaud et al (1999) and Breinholt et al (2000) suggested that flavinoids might be strong stimulants for mammalian reproduction, because they contain estrogen-like substances.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the nearest capture of C. castanea has been in Acre, Rio Branco, in the western Brazilian Amazon (Uieda, 1980). In Panamá, Carollia castanea and C. perspicillata overlap in habitat use and certain dietary resources (Thies et al, 1998). Both species eat Piper fruits but C. castanea is clearly a Piper specialist and may be thus strongly limited by the availability of these plants.…”
Section: Unsampled Speciesmentioning
confidence: 99%
“…Many zoologists assume-explicitly or implicitly-that trophic-resource partitioning is important for species coexistence, and this conviction has motivated a still-burgeoning literature on Neotropical bat diets and feeding behavior (e.g., Heithaus et al, 1975;Fleming et al, 1977;Bonaccorso, 1979;Bonaccorso and Gush, 1987;Thies et al, 1998;Dumont, 1999;Wendeln et al, 2000;Tschapka, 2004;Kalko, 2004, 2005;Rex et al, 2011;Andrade et al, 2013;Saldaña-Vázquez, 2014). Various trophicguild classifications have been defined on the basis of this research (LaVal and Fitch, 1977;Bonaccorso, 1979;Kalko et al, 1996), and trophic-guild membership is often used to assess Amazonian bat community structure (e.g., by Kalko and Handley, 2001;Lim and Engstrom, 2001;Bernard, 2002;Sampaio et al, 2003;Peters et al, 2006;Willig et al, 2007;Rex et al, 2008;Klingbeil and Willig, 2009;Bobrowiec and Gribel, 2010).…”
Section: Introductionmentioning
confidence: 99%